2001
DOI: 10.1046/j.1526-4610.2001.041007629.x
|View full text |Cite
|
Sign up to set email alerts
|

Periaqueductal Gray Matter Dysfunction in Migraine: Cause or the Burden of Illness?

Abstract: Objective.-The periaqueductal gray matter (PAG) is at the center of a powerful descending antinociceptive neuronal network. We studied iron homeostasis in the PAG as an indicator of function in patients with episodic migraine (EM) between attacks and patients with chronic daily headache (CDH) during headache. High-resolution magnetic resonance techniques were used to map the transverse relaxation rates R2, R2*, and R2 Ј in the PAG, red nucleus (RN), and substantia nigra (SN). R2 Ј is a measure of non-heme iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
474
2
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(503 citation statements)
references
References 22 publications
19
474
2
8
Order By: Relevance
“…It is generally accepted that the common forms of migraine with or without aura (Table 2): abnormal thickness, connectivity and/or activation of certain cortical and subcortical areas [24][25][26][27], increased transmitter [28] or iron content [29][30][31], decreased ATP content [32,33] and an abnormal pattern of sensory processing [34,35]. The latter is characterized by low amplitude of initial responses and hyperresponsivity with lack of habituation of late responses during repeated sensory stimuli [36], and has been attributed to a thalamocortical dysrhythmia caused by deficient monoaminergic control by brain stem nuclei (review in [37]).…”
Section: Chronic Migraine Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that the common forms of migraine with or without aura (Table 2): abnormal thickness, connectivity and/or activation of certain cortical and subcortical areas [24][25][26][27], increased transmitter [28] or iron content [29][30][31], decreased ATP content [32,33] and an abnormal pattern of sensory processing [34,35]. The latter is characterized by low amplitude of initial responses and hyperresponsivity with lack of habituation of late responses during repeated sensory stimuli [36], and has been attributed to a thalamocortical dysrhythmia caused by deficient monoaminergic control by brain stem nuclei (review in [37]).…”
Section: Chronic Migraine Pathophysiologymentioning
confidence: 99%
“…cortical sensitivity and % responsivity to sensory stimuli [35,36] % fractional anisotropy thalamus (MR-DTI) [43] ! cortical thickness and activation S1, temporal lobe [26] % cortical thickness and/or activation insula, cingulate, visual areas [24,26] % rs connectivity amygdala-insula [27] % iron content PAG and globus pallidus [29][30][31] % rs connectivity PAG-precuneus, visual [25] % tissue density in PAG [129] ! olfaction-induced trigeminal nucleus activation % pre-ictally [130] % subclinical posterior circulation infarcts [30] Chronic migraine % cortical sensitivity and !…”
Section: Episodic Migraine (Interictal)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies showed that brain white matter lesions increased with episode frequency, possibly demonstrating progression of the disease [6]. In addition, repetitive attacks may lead to chronic headache through a progressive impairment of the central antinociceptive system in the periaqueductal grey matter that controls activity of the trigeminovascular system [7]. In this context, prophylactic medication that acts to reduce the number of migraine attacks, more likely than abortive agents, might have a long-term effect on the natural evolutive history of migraine.…”
Section: Attack Frequencymentioning
confidence: 99%
“…Although this is a very small study, which requires confirmation by a larger controlled study, our data suggest a significant carryover effect in the young migraineur by administering short-term parenteral dihydroergotamine, dexamethasone and hydroxyzine. of the brainstem, may be operative in chronic headache syndromes [1,2]. Chronic central sensitisation caused by repetitive uncontrolled severe migraine attacks in a young person might lower the threshold for future attacks ultimately leading to an intractable, treatment-resistant malignant disease course in adult life.…”
mentioning
confidence: 99%